1Mx2.1, a novel high-molecular-weight glutenin subunit from Aegilops comosa and its relationship to high-quality dough. Issue 4 (1st August 2019) - Du, Xuye; Xia, Biya; He, Fang; Ren, Mingjian
Abstract: High-molecular-weight glutenin subunit (HMW-GS) of endosperm is mainly correlated with dough quality of bread wheat. In wheat cultivars, the HMW-GS genes with good processing quality are limited. However, there are an amount of excellent HMW-GS genes presenting in wheat-related species. In this work, two novel HMW-GS genes located on 1 M chromosome from Aegilops comosa have been cloned, designated as 1Mx2.1 and 1My12.1, respectively. The molecular structure of 1Mx2.1 and 1My12.1 showed high similarity with the published HMW-GS, but containing unique structures. 1Mx2.1 contained an extra cysteine residue in the repetitive domain, and 1My12.1 lost the conservative cysteine residue in the C-terminal domain. In vitro mixing test has indicated that 1Mx2.1 contributes excellent dough quality. The Ae. comosa can be used as an important genetic resource for wheat quality improvement.